2018
DOI: 10.1007/s00425-018-2917-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of enzyme activities in carnivorous pitcher plants of the genus Nepenthes

Abstract: Nepenthes regulates enzyme activities by sensing stimuli from the insect prey. Protein is the best inductor mimicking the presence of an insect prey. Carnivorous plants of the genus Nepenthes have evolved passive pitcher traps for prey capture. In this study, we investigated the ability of chemical signals from a prey (chitin, protein, and ammonium) to induce transcription and synthesis of digestive enzymes in Nepenthes × Mixta. We used real-time PCR and specific antibodies generated against the aspartic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 60 publications
4
21
0
Order By: Relevance
“…5) already showed high expression levels on D0. This corroborates findings that most of the endogenous secreted proteins already present in pitcher fluids before opening with certain proteins continuously replenished or induced by prey 15,34,37,46 . In comparison, there was no clear trend in the expression of transporters on D0 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…5) already showed high expression levels on D0. This corroborates findings that most of the endogenous secreted proteins already present in pitcher fluids before opening with certain proteins continuously replenished or induced by prey 15,34,37,46 . In comparison, there was no clear trend in the expression of transporters on D0 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The pitchers can detect enzymes in the pitcher fluids and respond accordingly to maintain an optimal cocktail of enzymes so that the benefits from prey digestion outweigh the costs of protein replenishment and pitcher metabolisms. Other studies also revealed that pitchers can regulate enzyme activities 24,46,58 . This is likely involving Ca 2+ and jasmonic acid (JA) signal transduction pathways 22 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This suggests that all four culicid morphospecies are equally tolerant of acidic conditions, rather than the existence of multiple species with different physiological tolerances that only co-occur in more moderate conditions. Prey capture induces fluid acidification [100,101], and an increase in nutrient availability could explain the relationship between high abundance of ants, other insect prey, and mites with low pH.…”
Section: Discussionmentioning
confidence: 99%